TWO NEW SPECIES OF ALPINIA (ZINGIBERACEAE) FROM SULAWESI, INDONESIA - WISNU H. ARDI; MARLINA ARDIYANI (Reinwardtia, 2015)
ARDI, W. H. & ARDIYANI, M. 2015. Two new species of Alpinia (Zingiberaceae) from Sulawesi, Indonesia. Reinwardtia 14(2): 311 - 316. - Two new species of Alpinia section Alpinia subsection Cenolophon, Alpinia macrocrista Ardiyani & Ardi, and Alpinia pusilla Ardi & Ardiyani, from Sulawesi, Indonesia, are described. Colour plates are provided, and four-locus DNA barcodes have been generated for the purpose of identification. Tabulated key to species of Alpinia subsection Cenolophon in Sulawesi is also presented.